Growth Of Business Partners On Sales Volume And Stock As Moderating Variables On Stock Points - Areu Nurbela; Eman Sulaiman; Suwandi (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — The purpose of this study is to identify the effect of business partner growth on sales volume with stock as a variable that affects the relationship between business partner growth and sales volume. The object of the study is business partners and sales of basic food products at the regular stock point of the Cirebon Palace. The phenomenon of an increase in the number of business partners that are relatively stable from month to month each period will be a positive thing for the growth process of a business partner, so that sales volume will increase if followed by adequate availability stock.Research method—In this study using quantitative methods and questionnaires became the source of data obtained from respondents. The analytical methods in this study are simple regression analysis and moderation regression analysis, validity test and reliability test, classical assumption test consisting of normality test, autocorrelation test, heteroskedasticity test, multicholinearity test, and hypothesis test which includes t test, f test and coefficient of determination.Result— The results showed that (1) the business partner growth variable has a positive effect on sales volume, (2) stock variables affect sales volume, (3) stock variables moderate the relationship between business partner growth variables and sales volume.Conclusion— this study found that the growth of business partners has a positive effect on sales volume in the basic food product industry. The availability of stock plays a crucial role in moderating this relationship, as adequate stock levels enhance the impact of business partner growth on sales volume. Therefore, businesses should focus on expanding their network of business partners while ensuring sufficient stock to maximize sales growth and capitalize on market opportunities.